3D Bioprinting-Based Vascularized Tissue Models Mimicking Tissue-Specific Architecture and Pathophysiology for in vitro Studies - Hwang, Dong Gyu; Choi, Yoo-mi; Jang, Jinah (Frontiers in Bioengineering and Biotechnology, 2021)
A wide variety of experimental models including 2D cell cultures, model organisms, and 3D in vitro models have been developed to understand pathophysiological phenomena and assess the safety and efficacy of potential therapeutics. In this sense, 3D in vitro models are an intermediate between 2D cell cultures and animal models, as they adequately reproduce 3D microenvironments and human physiology while also being controllable and reproducible. Particularly, recent advances in 3D in vitro biomimicry models, which can produce complex cell structures, shapes, and arrangements, can more accurately reflect in vivo conditions than 2D cell culture. Therefore, this review discusses the recent developments and key features of various types of 3D bioprinted tissues, particularly those associated with blood vessels and highly vascularized organs such as the heart, liver, and kidney. Moreover, this review also summarizes the current state of three categories of 3D bioprinting-based disease models according to their disease modeling approach. Finally, we propose the future directions of 3D bioprinting approaches for the creation of more advanced in vitro biomimetic 3D tissues, as well as the translation of 3D bioprinted tissue models to clinical applications.